Evaluating the Inhibitory Activity of Ferrocenyl Schiff Bases Derivatives on 5-Lipoxygenase: Computational and Biological Studies - Mascayano-Collado, C; Vasquez-Martinez, y; Godoy-Gonzalez, F; Godoy-Gonzalez, F; Muñoz-Osses, M; Muñoz-Osses, M; Flores-Vergara, E; Flores-Vergara, E; Navarrete-Tudela, E (Elsevier Inc., 2023)
In the search for new 5-LOX inhibitors, two ferrocenyl Schiff base complexes functionalized with catechol ((ƞ5-(E)-C5H4-N[dbnd]CH-3,4-benzodiol)Fe(ƞ5-C5H5) (3a)) and vanillin ((ƞ5-(E)-C5H4-N[dbnd]CH-3-methoxy-4-phenol)Fe(ƞ5-C5H5) (3b)) were obtained. Complexes 3a and 3b were biologically evaluated as 5-LOX inhibitors showed potent inhibition compared to their organic analogs (2a and 2b) and known commercial inhibitors, with IC50 = 0.17 ± 0.05 μM for (3a) and 0.73 ± 0.06 μM for (3b) demonstrated a highly inhibitory and potent effect against 5-LOX due to the incorporation of the ferrocenyl fragment. Molecular dynamic studies showed a preferential orientation of the ferrocenyl fragment toward the non-heme iron of 5-LOX, which, together with electrochemical and in-vitro studies, allowed us to propose a competitive redox deactivation mechanism mediated by water, where Fe(III)-enzyme can be reduced by the ferrocenyl fragment. An Epa/IC50 relationship was observed, and the stability of the Schiff bases was evaluated by SWV in the biological medium, observing that the hydrolysis does not affect the high potency of the complexes, making them interesting alternatives for pharmacological applications. © 2023 Elsevier Inc.